2004
DOI: 10.1016/s0093-934x(03)00454-1
|View full text |Cite
|
Sign up to set email alerts
|

Naming analog clocks conceptually facilitates naming digital clocks

Abstract: This study investigates how speakers of Dutch compute and produce relative time expressions. Naming digital clocks (e.g., 2:45, say ''quarter to three'') requires conceptual operations on the minute and hour information for the correct relative time expression. The interplay of these conceptual operations was investigated using a repetition priming paradigm. Participants named analog clocks (the primes) directly before naming digital clocks (the targets). The targets referred to the hour (e.g., 2:00), half pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…For both naming and reading alike, response latencies were determined by morphophonological factors, such as the number of phonemes and morphemes, and the log morpheme and whole-form frequencies. For clock time naming (i.e., arabic format), however, response latencies not only demonstrated the influence of morphophonological factors, but also of conceptual factors, reflecting the conceptual operations required in telling time in the Dutch language (see also Meeuwissen, Roelofs, & Levelt, 2004, 2005. In Dutch, time is told in a relative way, with time expressions not only making reference to the full hour, like in English, but also to the half hour (Bock, Irwin, Davidson, & Levelt, 2003).…”
mentioning
confidence: 99%
“…For both naming and reading alike, response latencies were determined by morphophonological factors, such as the number of phonemes and morphemes, and the log morpheme and whole-form frequencies. For clock time naming (i.e., arabic format), however, response latencies not only demonstrated the influence of morphophonological factors, but also of conceptual factors, reflecting the conceptual operations required in telling time in the Dutch language (see also Meeuwissen, Roelofs, & Levelt, 2004, 2005. In Dutch, time is told in a relative way, with time expressions not only making reference to the full hour, like in English, but also to the half hour (Bock, Irwin, Davidson, & Levelt, 2003).…”
mentioning
confidence: 99%
“…Deze bleek een invloed te hebben op de spraaklatenties voor de digitale klokken: een kleine afstand in minuten ten opzichte van de analoge klok resulteerde in snellere responstijden dan grotere afstanden. Blijkbaar verloopt het stadium van conceptuele voorbereiding gelijk voor het relatief benoemen van analoge en digitale klokken (Meeuwissen et al, 2004). Aansluitend werd een identieke studie uitgevoerd met Amerikaanse studenten, die een absolute tijdsaanduiding gebruiken (bijv.…”
Section: Kloktijdenunclassified
“…Currently, the Federal Aviation Administration (FAA) requires no minimum time requirement for reviewing analog clock metaphors. Meeuwissen, Roelofs, and Levelt (2004) found that more errors were committed when reading relative time (e.g., half past 2) from analog clocks than when reading from digital clocks. They also found that participants could say absolute (e.g., twothirty) times faster when reading from a digital clock when compared to an analog clock.…”
mentioning
confidence: 97%